LEGAL STATUS OF FOUNDATION PROPERTY CONSIDERED AS AN INHERITANCE BY THE FOUNDER'S FAMILY - Fikri Al Muhaddits Dalimunthe; Syafruddin Syam; Nurcahaya (RADJA PUBLIKA, 2026)
A foundation is a legal entity consisting of separated assets and allocated to achieve certain objectives in the social, religious and humanitarian fields, which does not have members. The existence of foundations in Indonesia as legal entities engaged in social activities is very necessary. This is also related to the provisions of the 1945 Constitution of the Republic of Indonesia which in several articles regulates these needs, including Article 27, Article 31 and Article 34 of the 1945 Constitution of the Republic of Indonesia shows that the government and society need the existence of social organizations. This study uses a normative juridical legal research method, aimed at examining legal principles, legal systematics, legal synchronization, legal history and comparison, descriptive analytical research, that research is included in the scope of research that describes, examines and explains precisely and analyzes applicable laws and regulations related to legal theory. The research source uses library data (library research), namely research conducted by citing sources from books, legislation and other regulations that have a relationship with the problem aspect. The results of this study are that there is no authority of the founding family over the foundation they established, so there is no right to obtain the results from the management of the foundation in the form of inheritance or other forms except for the separation of assets between the foundation's assets and personal assets, so the distribution of inheritance from the foundation's assets that are not separated is prohibited. In the event that the will as intended to establish the Foundation is not executed, then at the request of the interested party, the Court can order the heirs or recipients of the will concerned to execute the will. This provision accommodates a person's wishes before dying to establish a Foundation, and is stated in a will.